Respuesta :

Answer:

x = 3 and y = -1

Step-by-step explanation:

It is given that,

3x + 2y = 7   ----(1)

2x - 5y = 11    ---(2)

To find the solution of given equations

eq(1) * 2 ⇒

6x + 4y = 14    ----(3)

eq(2) * 3 ⇒

6x - 15y = 33  ----(4)

eq(3) - eq(4) ⇒

6x + 4y = 14    ----(3)

6x - 15y = 33 ----(4)

        19y = 19

y = -1

Substitute the value of y in eq (1) we get,

3x + 2y = 7   ----(1)

3x + (2 *-1) = 7

3x = 7 + 2 = 9

x = 9/3 = 3

Therefore x = 3 and y = -1

Answer:

[tex]x=3,\ \ y=-1[/tex]

Step-by-step explanation:

We have the following two equations:

[tex]3x+2y=7[/tex]

[tex]2x-5y=11[/tex]

To solve the system by the elimination method multiply the first equation by [tex]\frac{5}{2}[/tex] and add it to the second equation

By multiplying the first equation by [tex]\frac{5}{2}[/tex] you get the following:

[tex]\frac{15}{2}x+5y=\frac{35}{2}[/tex]

Now we add the two equations

[tex]\frac{15}{2}x+5y=\frac{35}{2}[/tex]

[tex]2x-5y=11[/tex]

---------------------------------------------------------

[tex]\frac{19}{2}x=\frac{57}{2}\\\\19x=57\\\\x=\frac{57}{19}\\\\x=3[/tex]

Now substitute the value of x in either equation and solve for y

[tex]2(3)-5y=11[/tex]

[tex]6-5y=11[/tex]

[tex]-5y=11-6[/tex]

[tex]-5y=5[/tex]

[tex]y=-1[/tex]